Strategi Dakwah Majlis Ta’lim Assa-adah pada Kelompok Marjinal - Qolbi, Muhammad Fatihul; Sukataman, Sukataman; Darmaningrum, Khaerunnisa Tri (IAINU Kebumen, 2025)
This research discusses the da'wah strategy or methods of assa-adah ta'lim assembly for marginalized groups. Title: Da'wah Strategy for Marginalized Groups in Gang Beard Society V. Marginalized groups are often marginalized, vulnerable, and difficult to reach by religious preaching, so a special approach is needed to deliver religious messages and support positive changes in their lives. Majlis ta'lim assa-adah has succeeded in implementing a da'wah strategy to marginalized groups by approaching them to improve religious knowledge and other factors to empower themselves to approach Allah SWT. Da'wah is not only about religious messages, but also about helping marginalized groups to improve their lives. The program strategy implemented by the Majlis Ta'lim Assa-Adah is by holding a routine reading of the Koran every Wednesday night and the village Koran every Saturday to Thursday and has succeeded in implementing it. Don't forget the various factors that overcome the various characteristics of a marginal person. This research emphasizes the importance of understanding the uniqueness of each marginalized group and developing strategies tailored to their needs, so that religious messages can be conveyed in a relevant way and build strong relationships between da'wah and these marginalized groups.